THE EFFECTS OF VOCABULARY AND GRAMMAR MASTERY TOWARDS STUDENTS’ SPEAKING SKILLS AT SMK KABUPATEN CIREBON - S, Cici; Oom (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study aimed to investigate the effects of Vocabulary Mastery and Grammar Mastery on students' speaking skills at SMK Kabupaten Cirebon. A survey research design was employed to collect empirical data. The research instruments were validated and reliable, with Cronbach's Alpha exceeding 0.60. Data normality and heteroscedasticity tests were conducted, confirming the suitability of multiple regression analysis. Data collection involved both library and field research, including questionnaires assessing Vocabulary Mastery, Grammar Mastery, and Speaking Skills. The findings revealed a significant joint effect of Vocabulary Mastery and Grammar Mastery on students' speaking skills (Sig. = 0.000, F observed = 111.121). Furthermore, individual analyses demonstrated significant effects of both Vocabulary Mastery (Sig. = 0.000) and Grammar Mastery (Sig. = 0.000) on students' speaking skills. These findings underscore the crucial roles of vocabulary and grammar proficiency in enhancing speaking abilities among students at SMK Kabupaten Cirebon